2020
DOI: 10.1001/jamanetworkopen.2020.4721
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Value of Tumor Variation Profiling Perceived by Patients With Cancer

Abstract: IMPORTANCEUse of tumor molecular profiling (MP) is entering routine clinical practice; however, little is known about how much and why patients value MP. OBJECTIVE To examine the perceived value of MP to patients with advanced cancer and factors associated with perceived value. DESIGN, SETTING, AND PARTICIPANTSA cross-sectional survey that included willingness-to-pay trade-off scenarios was administered to participants after consent and before MP. A total of 777 participants (94% response rate) were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This association between WTP for cancer-related interventions and demographic characteristics is consistent with other studies. A number of studies have indicated that WTP monetary values are positively influenced by race/ethnicity [ 42 46 ], similar to our findings for the WTP of Jews versus other ethnic groups. As found here, most studies have shown that WTP amounts increase with respondent income [ 17 , 31 , 35 , 44 , 46 81 ].…”
Section: Discussionsupporting
confidence: 89%
“…This association between WTP for cancer-related interventions and demographic characteristics is consistent with other studies. A number of studies have indicated that WTP monetary values are positively influenced by race/ethnicity [ 42 46 ], similar to our findings for the WTP of Jews versus other ethnic groups. As found here, most studies have shown that WTP amounts increase with respondent income [ 17 , 31 , 35 , 44 , 46 81 ].…”
Section: Discussionsupporting
confidence: 89%
“…Table 1 includes three publications [7][8][9] from a single survey of 100 patients with breast cancer recruited during their first visit to the University of Texas MD Anderson Cancer Center who were asked to provide consent for tissue banking. Table 2 includes three publications [10][11][12] from the Psychosocial Issues in Genomics in Oncology (PiGeOn) Project, a substudy of the Molecular Screening and Therapeutics Program in Sydney, Australia, which provided tumor molecular profiling to 1,000 patients with advanced cancer for whom there are no further therapeutic options. Table 2 also includes two publications by Blijsma et al [13,14] who interviewed patients (twice) regarding attitudes toward secondary germline findings from tumor NGS and then, shortly thereafter, conducted a third set of more in-depth interviews with the same patients, summarized in a separate publication.…”
Section: Patientsmentioning
confidence: 99%
“…Qualitative studies have reported that patients with advanced cancer offered tumor testing had positive views about, and unequivocally accepted, screening for somatic tumor genetic variants linked to possible cancer treatments (Best et al, 2019; Best et al, 2020; Hamilton et al, 2017; Liang et al, 2017). In a quantitative assessment of advanced cancer patients' perceived value of CGTP, we found that as many as 89% of such patients would have CGTP for as little as a 1% actionable return rate (Butow, Davies, et al, 2020). In these studies, patients perceived CGTP to have high importance even though they had had poor to moderate knowledge of CGTP (Davies et al, 2020; Liang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%